Adoption and Focus: Practical Linear Types for Imperative Programming - Fahndrich, Manuel; DeLIne, Robert (Proceedings of the 2002 ACM SIGPLAN Conference on Programming Language Design and Implementation (PLDI), 2002)
A type system with linearity is useful for checking software protocols and resource management at compile time. Linearity provides powerful reasoning about state changes, but at the price of restrictions on aliasing. The hard division between linear and nonlinear types forces the programmer to make a trade-off between checking a protocol on an object and aliasing the object. Most onerous is the restriction that any type with a linear component must itself be linear. Because of this, checking a protocol on an object imposes aliasing restrictions on any data structure that directly or indirectly points to the object. We propose a new type system that reduces these restrictions with the adoption and focus constructs. Adoption safely allows a programmer to alias objects on which she is checking protocols, and focus allows the reverse. A programmer can alias data structures that point to linear objects and use focus for safe access to those objects. We discuss how we implemented these ideas in the Vault programming language.